An Analysis of Figurative Language in Jalaluddin Rumi’s Quotes in Book The Meaningful Life With Rumi - Putra, Imam Soekarno; Puspitasari, Anita (CV. Ridwan Publisher, 2020)
This research is aimed to know and comprehend about figurative language which is used by Jalaluddin Rumi’s quotes. The main problem in this research are to know kinds of figurative language, literal meaning and the dominant of figurative language are found in Jalaluddin Rumi’s quotes. The primary source is from book “The meaningful life with Rumi” which was edited by Abd. Kholiq. There are 212 quotes on it which contain poems and proverbs. The writer analyzes 60 quotes. The second data source is taken from Laurence Perrine, Gorys Keraf and others that are related to the things which are going to be analyzed. This research uses qualitative research method. The data are collected, classified, identified and explained by giving the evidence from the statements. The writer only focuses four types of figurative language that are metaphor, personification, overstatement, and simile. Based on the result of this research, the writer concludes that in Jalaluddin Rumi’s quotes uses figurative language and there is literal meaning. The writer also has found 75 figurative language in Jalaluddin Rumi’s quotes from 60 quotes in the book of “The Meaningful Life with Rumi”. The writer has concluded the most of dominant figurative language which is utilized in Jalaludin Rumi’s quotes is metaphor with the total 23 statements, the second is simile with the total 22 statements, the third is overstatement with the total 16 statements and the last is personification with the total 14 statements. The most of Jalaluddin Rumi’s quotes talk about love, faith, hope, soul, virtue and determination. Keywords: Figurative language; Jalaluddin Rumi’s quotes and Literal meaning.